PENDAMPINGAN KEPADA WAJIB PAJAK DALAM PELAPORAN SPT MENUJU KEPATUHAN PEMBAYARAN PAJAK ORANG PRIBADI - Riana Rachmawati Dewi; Purnama Siddi; Kartika Hendra Titisari (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2020)
Education on the importance of taxes and awareness of paying taxes is part of the Directorate General of Tax's strategy to increase state revenue, which in turn will be returned to the public. Another form of education that has begun to be developed is a collaboration program with the community in the field of education by cooperating with tertiary institutions with the Tax Volunteer program which is part of community service. The method of implementing Community Service follows the rules set by the Directorate General of Taxes, which mainly involves coaching in the form of training and assistance to the community. The expected goal is to provide assistance to the public in reporting the SPT OP in 2019. The PKM team placed at KPP Surakarta has provided assistance to OP taxpayers both at the KPP Surakarta and direct picup action by visiting the taxpayer's work location.